Synthesis and Characterization of Organic-Inorganic Nanocomposite Poly-o-anisidine Sn(IV) Arsenophosphate: Its Analytical Applications as Pb(II) Ion-Selective Membrane Electrode - Asif Ali Khan; Umme Habiba; Anish Khan (International Journal of Analytical Chemistry)
Poly-o-anisidine Sn(IV) arsenophosphate is a newly synthesized nanocomposite material and has been characterized on the basis of its chemical composition, ion exchange capacity, TGA-DTA, FTIR, X-RAY, SEM, and TEM studies. On the basis of distribution studies, the exchanger was found to be highly selective for lead that is an environmental pollutant. For the detection of lead in water a heterogeneous precipitate based ion-selective membrane electrode was developed by means of this composite cation exchanger as electroactive material. The membrane electrode is mechanically stable, with a quick response time, and can be operated over a wide pH range. The selectivity coefficients were determined by mixed solution method and revealed that the electrode is sensitive for Pb(II) in presence of interfering cations. The practical utility of this membrane electrode has been established by employing it as an indicator electrode in the potentiometric titration of Pb(II).